-x-3-5/6x=-53/3

Simple and best practice solution for -x-3-5/6x=-53/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-3-5/6x=-53/3 equation:


x in (-oo:+oo)

-x-((5/6)*x)-3 = -53/3 // + -53/3

-x-((5/6)*x)-(-53/3)-3 = 0

(-5/6)*x-x+53/3-3 = 0

44/3-11/6*x = 0 // - 44/3

-11/6*x = -44/3 // : -11/6

x = -44/3/(-11/6)

x = 8

x = 8

See similar equations:

| -6n-1/2-3/7n=983/14 | | 16/3=-2/3d-4/5d-2 | | 1/5m+7+4m=14/5 | | (5(1-3x)/2)+10x=0 | | 2/9-5w-5/6w=113/36 | | 2/9+3d+4d=113/36 | | -t+9-4t=-1 | | 8x+5y=-19 | | 2t+5+2/3t=29/9 | | -107/18=-1/2a+6a-4/9 | | 1+n+7n=-9/7 | | -31/21=3b-b-1/7 | | 5d+1+2/5d=248/5 | | 7x+4+5/7x=46/7 | | -41/7=4/7n+1/3n+5 | | -37/5=-2/5m+m-4/5 | | 10-2/3b+1/7b=29/3 | | -3/8-7n+1/5n=-577/88 | | 1/2x-2+x=-11/4 | | 5w-3-5/6w=-73/66 | | -5t+10+3/7t=422/7 | | 1/2-2n-n=-1/2 | | (4x^2)+16x=0 | | 1/2-3/5w+4w=413/10 | | x/4=(x/6)+1 | | 1/3d+8-d=32/3 | | -107/7=3n-6/7n-2/7 | | n-9+2/5n=-433/45 | | m+2*5=m*11 | | 2/9+4t+4t=446/63 | | 1/3k+2/7+k=-38/63 | | 2/9-a+3a=38/9 |

Equations solver categories